DIFUSI INOVASI SI D’NOK DALAM PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KOTA SEMARANG - Deo Budhi Anggitlistio; Hardi Warsono; R. Slamet Santoso (Journal of Public Policy and Management Review, 2023)
The need for public services that are easy and fast, especially in 2020 the Covid-19 pandemic occurred which caused all offline services to be closed. SI D'nOK innovations are created and disseminated. However, people's knowledge of the D'nOK SI application and the operation of the D'nOK SI application are still very poor. This is the background of this research. This study aims to analyze the diffusion of innovations and the obstacles that occur in the diffusion of innovations in D'nOK SI applications in providing population administration services in the city of Semarang. The research method used is descriptive qualitative with data collection techniques of interviews, observation and documentation. This study uses the theory of innovation diffusion according to Everett M. Rogers, namely innovation, communication channels, timeframe, and social systems to obstacles in the diffusion of innovations. The results of the study show that the diffusion of D'nOK SI innovations has been going well. This is supported by convenience and benefits in the form of effective, efficient and in accordance with community needs. The community knows SI D'nOK based on interpersonal channels and mass media channels. The timeframe for receiving is long and influenced by authority figures. However, the lack of human resources and operators doing double duty causes the service to take longer. From this past experience, it will influence the deployment of SI D’nOK innovations in the future.